Dips and their uses - Oman, Harry G. F. (My University, 1907)
Introduction: It has been said that nine farmers out of every ten treat their live-stock exactly as they treat themselves; that is to say when they feel out of sorts they take a dose of physic and if that does not help they go to the doctor and learn when it is too late, that they have a serious disease which might have been prevented with a little caution, or cured if attended to earlier. There is a tendency to underestimate the economic importance of external parasites and parasitic diseases, especially those parasites that do not cause scabby formations on the skin as the injurious effect produced by them is not always recognized as being parasitic in origin. The animal apparently is in a healthy condition but they do not do well, the irritation and annoyance caused by the parasites prevent them from making a vigorous growth, which reduces their constitution and makes them more liable to disease. Animals that are weak and out of condition invite disease germs and in this way a herd may become infected with a serious disease. Much of the enormous loss to breeders and stockmen caused by parasites and diseases can be prevented, stopped and cured by the farmers themselves. That the parasites and diseases have developed to the extent that they now have is due large to the carlesness of the stockmen and to the lax government regulations, as they can easily be prevented or extirminated if proper precautions are taken and the proper measures observed in affecting the cure.
Citation: Oman, Harry G. F. Dips and their uses. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Infectious Diseases; Treating Disease; Diseases in Livestock; Theses